2021
DOI: 10.47836/pjst.29.2.05
|View full text |Cite
|
Sign up to set email alerts
|

The Built Environment and its Impact on Transit based Transportation Users Walking Activity in Semarang, Indonesia

Abstract: The increase in mobility rate due to the current rise in population has become a challenge in urban development. This led to the development of pedestrian walkways, which are integrated with transit-based transportation, to minimize problems due to the high level of mobility of the urban population. According to some experts, environmental conditions are one of the main factors capable of affecting pedestrians' frequency. Therefore, this study explores the effect of the built environment, such as density, dive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 22 publications
(39 reference statements)
0
2
0
Order By: Relevance
“…Users who choose to walk to their stop typically cover distances of less than 1 kilometer. This makes sense because the average travel distance for users to reach public transportation is around 300 meters (Rakhmatulloh, et al, 2021). This result is also in line with research by Zhu (2022) that most bicycle trips are short-distance trips with Euclidean distances of less than 1 km.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Users who choose to walk to their stop typically cover distances of less than 1 kilometer. This makes sense because the average travel distance for users to reach public transportation is around 300 meters (Rakhmatulloh, et al, 2021). This result is also in line with research by Zhu (2022) that most bicycle trips are short-distance trips with Euclidean distances of less than 1 km.…”
Section: Discussionsupporting
confidence: 84%
“…Yogyakarta's land use is mainly characterized by a prominent trade and service area, especially following the main road. Research conducted by Rakhmatulloh, Dewi, & Nugraheni (2021) shows that usually the area has the highest balance because it is a function of the area that combines residential land with trade and services. This is supported by the fact that trade and services in Yogyakarta are mostly household-based.…”
Section: Land Usementioning
confidence: 99%
“…The closer to one, the better the land use balance value in an area [25]. Research conducted by Rakhmatulloh et al (2021) found that land use for trade and services is one of the highest factors in generating movement from the outskirts of the city to the city center or vice versa. It also really depends on the characteristics of the community and the geographical conditions of the region.…”
Section: Development Of Built Environment For Urban Street Designmentioning
confidence: 99%
“…The impact of these trends is largely unknown because there is still very little research on walking in Indonesia's cities. While some studies have analysed factors influencing the propensity for walking in Indonesia (for example, influence of urban form, land-use mix, accessibility, population density, and so on) [7][8][9][10][11], and the relationships between walking and health [12], few studies of Indonesian cities consider walking from the perspective of people's affective experiences of places or their "sense of place".…”
Section: Introductionmentioning
confidence: 99%